PENGARUH VIDEO ANIMASI DONGENG TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI TAMAN KANAK KANAK NEGERI PEMBINA LUBUK SIKAPING - Dini Safitri, Rahma; Anggraini, Vivi; Pransiska, Rismareni; Muryanti, Elise (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking A crucial component of early childhood language development is ability because It helps kids in expressing ideas, experiences, and feelings during everyday interactions. Difficulties in speaking ability were still found among kids of Taman Kanak-Kanak Negeri Pembina Lubuk Sikaping who are five to six years old, including limited vocabulary, difficulties in constructing simple sentences, limited fluency in answering questions, and low confidence in expressing opinions. These conditions indicate the need for learning media that are engaging and appropriate to children's learning characteristics. The purpose of this study was to ascertain how animated fairy tale movies affected the speaking abilities of youngsters between the ages of five and six. Using a pretest-posttest control group design and a quasi-experimental methodology, the study used a quantitative approach. There were 26 kids involved, including 13 kids in the experimental group and 13 kids in the control group. Observation was used to gather data using a speaking ability assessment instrument and examined utilizing the independent samples t-test, homogeneity, and normalcy methods. The outcomes shown an improvement in this speaking ability from children in this trial group after receiving treatment through animated fairy-tale videos. The mean pretest score for the experimental group rose from 9.23 to 17.77 on the posttest, while the controls group's mean score increased from 9.08 to 14.15. There was a significant difference between the two groups, as indicated by the independent samples t-test's significance value of less than 0.001. Animated fairy-tale videos can therefore be utilized as an alternate teaching method to encourage youngsters between the ages of five and six to talk.